The role of oxygen depletion and subsequent radioprotective effects during irradiation of mosquito pupae in water - Yamada, Hanano (Parasit Vectors, 2020)
BACKGROUND: Radiation induced sterility is the basis of the Sterile Insect Technique, by which a target insect pest population is suppressed by releasing artificially reared sterile males of the pest species in overflooding numbers over a target site. In order for the sterile males to be of high biological quality, effective standard irradiation protocols are required. Following studies investigating the effects of mosquito pupae irradiation in water versus in air, there is a need to investigate the oxy-regulatory behavior of mosquito pupae in water to better understand the consequences of irradiation in hypoxic versus normoxic conditions. METHODS: Pupae of Aedes aegypti, Ae. albopictus, and Anopheles arabiensis were submerged in water inside air-tight 2 ml glass vials at a density of 100 pupae/ml and the dissolved oxygen (DO) levels in the water were measured and plotted over time. In addition, male pupae of Ae. aegypti (aged 40–44 h), Ae. albopictus (aged 40–44 h) and An. arabiensis (aged 20–24 h) were irradiated in a gammacell220 at increasing doses in either hypoxic (water with < 0.5% O(2) content) or normoxic (in air) conditions. The males were then mated to virgin females and resulting eggs were checked for induced sterility. RESULTS: All three species depleted the water of DO to levels under 0.5% within 30 minutes, with An. arabiensis consuming oxygen the fastest at under 10 minutes. Following irradiation, the protective effect of hypoxia was observed across species and doses (P < 0.0001), increasing at higher doses. This effect was most pronounced in An. arabiensis. CONCLUSIONS: The consumption of dissolved oxygen by pupae submerged in water was significantly different between species, indicating that their oxy-regulatory capacity seems to have possibly evolved according to their preferred breeding site characteristics. This needs to be considered when sterilizing male mosquitoes at pupal stage in water. Depending on species, their DO consumption rates and their density, irradiation doses needed to achieve full sterility may vary significantly. Further assessments are required to ascertain optimal conditions in terms of ambient atmosphere during pupal irradiation to produce competitive sterile males, and temperature and density dependent effects are expected. [Image: see text]